Decoding a criminal - Han, Barb (Behavioral Analysis Unit series, 2021)
He needs her to solve a crime. He wants her for so much more. Dashiell West's sister is in trouble. Big trouble. And recruiting computer whiz Raina Andress to work with him in cybercrimes at the Behavioral Analysis Unit is his only hope. Raina knows her friend would never embezzle millions. But join forces with the sexy agent from her past and risk her heart again? Dangerous. Tracking a deadly mastermind willing to sacrifice them all for his nefarious plan? Deadly.